2009
DOI: 10.1371/journal.pone.0008323
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rescue-Thrombolysis during Cardiopulmonary Resuscitation in Patients with Pulmonary Embolism

Abstract: BackgroundCardiac arrest in patients with pulmonary embolism (PE) is associated with high morbidity and mortality. Thrombolysis is expected to improve the outcome in these patients. However studies evaluating rescue-thrombolysis in patients with PE are missing, mainly due to the difficulties of clinical diagnosis of PE. We aimed to determine the success influencing factors of thrombolysis during resuscitation in patients with PE.Methodology/Principal FindingsWe analyzed retrospectively the outcome of 104 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…37,[45][46][47][48][49][50][51][52][53][54] There is no consensus on the ideal dose of thrombolytic therapy in PE-associated cardiac arrest. Contemporary examples of accelerated emergency thrombolysis dosing regimens for fulminant PE include alteplase 50 mg intravenous (IV) bolus with an option for repeat bolus in 15 minutes, or single-dose weight-based tenecteplase; thrombolytics are administered with or followed by systemic anticoagulation.…”
Section: Confirmed Pulmonary Embolismmentioning
confidence: 99%
See 1 more Smart Citation
“…37,[45][46][47][48][49][50][51][52][53][54] There is no consensus on the ideal dose of thrombolytic therapy in PE-associated cardiac arrest. Contemporary examples of accelerated emergency thrombolysis dosing regimens for fulminant PE include alteplase 50 mg intravenous (IV) bolus with an option for repeat bolus in 15 minutes, or single-dose weight-based tenecteplase; thrombolytics are administered with or followed by systemic anticoagulation.…”
Section: Confirmed Pulmonary Embolismmentioning
confidence: 99%
“…[55][56][57] Early administration of systemic thrombolysis is associated with improved resuscitation outcomes compared with use after failure of conventional ACLS. 46 Successful surgical and percutaneous mechanical embolectomy in cases of PE-related cardiac arrest have been reported in limited series. [58][59][60] Many of these patients developed cardiac arrest before or during embolectomy.…”
Section: Confirmed Pulmonary Embolismmentioning
confidence: 99%
“…Since then, more than 100 cases of successful administration of thrombolysis in patients with confirmed or suspected PE during CPR have been published, when the thrombolysis was almost always used as a last resort [8]. Besides case series, clinical studies have also confirmed the effectiveness of thrombolysis [9,10]. However, currently, the use of thrombolysis in CA caused by PE has not been supported by prospective, randomized, controlled trials.…”
mentioning
confidence: 99%
“…[56][57][58] Thombolysis Humans No treatment benefit from routine use in OHCA patients. May be useful in selected patients with STEMI and pulmonary embolism [61][62][63] Neurotensin Animals Prolonged decrease of body temperature. 64 ATP-sensitive potassium channel activators.…”
Section: Humans Nrtsmentioning
confidence: 99%
“…Thereafter, only a few reports from retrospective cohorts of patients show possible benefits from thrombolytic therapy in certain subgroups of patients with pulmonary embolism and STEMI. 62,63 Thrombolytic therapy is indicated post-ROSC in patients with STEMI and no possibility for invasive reperfusion. 48 …”
Section: Thrombolysismentioning
confidence: 99%